Features of Visually AcceSAble Rembrandt Images: Interrater Reliability in Pediatric Brain Tumors - Biswas, A.; Amirabadi, A.; Wagner, M.W.; Ertl-Wagner, B.B. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: At present, no evidence-based lexicon exists for pediatric intracranial tumors. The Visually AcceSAble Rembrandt Images terminology describes reproducible MR imaging features of adult gliomas for prediction of tumor grade, molecular markers, and survival. Our aim was to assess the interrater reliability of the pre-resection features of Visually AcceSAble Rembrandt Images in pediatric brain tumors.MATERIALS AND METHODS: Fifty consecutive pre-resection brain MR imaging examinations of pediatric intracranial neoplasms were independently reviewed by 3 neuroradiologists. The intraclass correlation coefficient for continuous variables and the Krippendorf alpha were used to evaluate the interrater agreement. Subgroup analysis was performed for 30 gliomas.RESULTS: Parameters with almost perfect agreement (α > .8) included tumor location (F1) and proportion of enhancing tumor (F5). Parameters with substantial agreement (α = .61–.80) were side of tumor epicenter (F2), involvement of eloquent brain (F3), enhancement quality (F4), proportion of non-contrast-enhancing tumor (F6), and deep white matter invasion (F21). The other parameters showed either moderate (α = .41–.60; n = 11), fair (α = .21–.40; n = 5), or slight agreement (α = 0–.20; n = 1). Subgroup analysis of 30 gliomas showed almost perfect agreement for tumor location (F1), involvement of eloquent brain (F3), and proportion of enhancing tumor (F5); and substantial agreement for side of tumor epicenter (F2), enhancement quality (F4), proportion of noncontrast enhancing tumor (F6), cysts (F8), thickness of enhancing margin (F11), and deep white matter invasion (F21). The intraclass correlation coefficient for measurements in the axial plane was excellent in both the main group (0.984 [F29] and 0.982 [F30]) and the glioma subgroup (0.973 [F29] and 0.973 [F30]).CONCLUSIONS: Nine features of Visually AcceSAble Rembrandt Images have an acceptable interrater agreement in pediatric brain tumors. For the subgroup of pediatric gliomas, 11 features of Visually AcceSAble Rembrandt Images have an acceptable interrater agreement. The low degree of reproducibility of the remainder of the features necessitates the use of features tailored to the pediatric age group and is likely related to the more heterogeneous imaging morphology of pediatric brain tumors.VASARIVisually AccesSAble Rembrandt ImagesREMBRANDTREpository for Molecular BRAin Neoplasia DaTA